2019
DOI: 10.1186/s41239-019-0153-2
|View full text |Cite
|
Sign up to set email alerts
|

Staff and student views of lecture capture: a qualitative study

Abstract: Many universities now use lecture capture. We used focus groups to investigate perceptions of lectures and their capture in staff (N = 8) and students (N = 17). We found that staff and students held different views of lectures and this impacted on their perceptions of lecture capture. Our findings confirmed a range of previously identified uses of lecture capture and additionally demonstrated its use to model expert behaviour. Furthermore, we report here that students felt lecture capture reduced anxiety, part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 46 publications
4
45
1
3
Order By: Relevance
“…Additionally, students generally agreed on the usefulness of recorded lectures across the three years of study. This agrees with previously reported findings on student preference of lecture capture as a facilitating tool in education (DiVall et al, 2013;Dommett et al, 2019). However, the median attitude toward actual use shifted from 'agree' in 2015 and 2018 (student lecture recording) to 'neutral' in 2020 (instructor provided commentary).…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, students generally agreed on the usefulness of recorded lectures across the three years of study. This agrees with previously reported findings on student preference of lecture capture as a facilitating tool in education (DiVall et al, 2013;Dommett et al, 2019). However, the median attitude toward actual use shifted from 'agree' in 2015 and 2018 (student lecture recording) to 'neutral' in 2020 (instructor provided commentary).…”
Section: Discussionsupporting
confidence: 91%
“…Educational data mining and state-of-the-art There has been a lot of progress in the current literature about using data obtained from the educational settings to improve the intended processes (Wang & Zhu, 2019;Abu Zohair, 2019, Exter et al, 2019Munro, 2018;Dommett, Gardner, & van Tilburg, 2019;Alizadeh, Mehran, Koguchi, & Takemura, 2019). It is noteworthy that existing research has demonstrated that HEIs are increasingly datahungry, with the stakeholders (students, teachers, and administrators, for example) seeking data and study results for their own needs and use (Clark, 2015;Williamson, 2018).…”
Section: Conceptualizing Text Mining For Teaching and Learning Assessmentioning
confidence: 99%
“…Several institutions have had to integrate emerging educational technologies in their different activities to maintain or sustain the credibility and quality of their business models or operations in general (Kori, Pedaste, & Must, 2018). Therefore, recent research (Wang & Zhu, 2019;Abu Zohair, 2019, Exter et al, 2019Munro, 2018;Dommett et al, 2019;Alizadeh et al, 2019;Kori et al, 2018) has focused on overcoming some of the challenges within the educational processes to provide opportunities for innovative teaching and learning methods (e.g., through educational data mining).…”
Section: Information Technologies For Quality Education and Innovationmentioning
confidence: 99%
See 2 more Smart Citations